Arctic researches, and, Life among the Esquimaux : being the narrative of an expedition in search of Sir John Franklin, in the years 1860, 1861, and 1862 - Hall, Charles Francis, 1821-1871. (New York : Harper & Brothers, 1865)
Published in England under title: Life with the Esquimaux: a narrative of Arctic experience in search of survivors of Sir John Franklin's expedition. Added t.p. engraved: Hall's arctic research expedition, and Life among the Esquimaux. Publisher's advertisements: 4 pages at end of text. "With maps and one hundred illustrations." Mode of access: Internet.